Intensitas penggunaan gawai dan kontrol orang tua di RT 02/RW 04 Desa Tambahagung - Windi Widyayati; Deka Setiawan; Siti Masfuah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to analyze the social interactions in using gadgets of 10-year-old children in Desa Tambahagung viewed from the control and the intensity of using gadget. The benefit of this study was analyzing the form of changes in social interactions that occurred in children aged 10 years who used gadgets. This study described 10 years old children affected by the gadget. This study used a qualitative phenomenological method, which was conducted in Desa Tambahagung RT 04/RW 02. The objects of this research were ten 10-year-old children in the area who were already familiar with gadgets, especially during the Covid 19 pandemic, in which they were closer and often used gadgets as a means of communication and learning because schools had switched to online learning. Data were collected through observation, interviews, documentation, and recording. The results showed that using gadgets on the interaction of children aged 10 years did not show a significant problem because on average children were extrovert or open to others. They generally played gadgets together with their friends so that the communication and interaction was still good. The phenomenon that emerged in this study was that the device had an effect on children's emotions, nomophobia, children's self-disclosure with parents, and children's language.